Deciphering the miRNA transcriptome of granulosa cells from dominant and subordinate follicles at first follicular wave in goat - Jinzhu Meng; Yuanyuan Zhao; Xingchao Song; Qingming An; Zhenyang Wu (Animal Biotechnology, 2024)
In goats, most follicles in the ovaries will be atresia and only a few dominant follicles (DFs) may eventually mature and ovulate at a follicular wave. To investigate the potential microRNAs (miRNAs) that regulate the expression of genes associated with follicular dominance or atresia, small RNA sequencing was performed on granulosa cells of DF and subordinate follicle at the first follicular wave in goats. A total of 108 differentially expressed miRNAs were detected in the two types of follicle granulosa cells: 16 upregulated miRNAs and 92 downregulated miRNAs. Kyoto Encyclopedia of Genes and Genomes analysis of the target genes showed that TKTL1, LOC102187810, LOC102184409 and ALDOA are closely associated with follicle dominance and are involved in the pentose phosphate pathway. Furthermore, a coexpression network of miRNAs and follicular dominance-related genes was constructed. The qPCR results well correlated with the small RNA sequencing data. Our findings provide new insight for exploring the molecular mechanism of miRNAs in regulating follicular development in goats.